Novel Push-Pull Benzodithiophene-Containing Polymers as Hole-Transport Materials for Efficient Perovskite Solar Cells - Aleksandra N. Mikheeva; Ilya E. Kuznetsov; Marina M. Tepliakova; Aly Elakshar; Mikhail V. Gapanovich; Yuri G. Gladush; Evgenia O. Perepelitsina; Maxim E. Sideltsev; Azaliia F. Akhkiamova; Alexey A. Piryazev; Albert G. Nasibulin; Alexander V. Akkuratov (Molecules, 2022)
Donor-acceptor conjugated polymers are considered advanced semiconductor materials for the development of thin-film electronics. One of the most attractive families of polymeric semiconductors in terms of photovoltaic applications are benzodithiophene-based polymers owing to their highly tunable electronic and physicochemical properties, and readily scalable production. In this work, we report the synthesis of three novel push–pull benzodithiophene-based polymers with different side chains and their investigation as hole transport materials (HTM) in perovskite solar cells (PSCs). It is shown that polymer P3 that contains triisopropylsilyl side groups exhibits better film-forming ability that, along with high hole mobilities, results in increased characteristics of PSCs. Encouraging a power conversion efficiency (PCE) of 17.4% was achieved for P3-based PSCs that outperformed the efficiency of devices based on P1, P2, and benchmark PTAA polymer. These findings feature the great potential of benzodithiophene-based conjugated polymers as dopant-free HTMs for the fabrication of efficient perovskite solar cells.